Effects of neuromuscular electrical stimulation on glycemic control: a systematic review and meta-analysis - Sanchez, Michael J.; Mossayebi, Ali; Sigaroodi, Solmaz; Apaflo, Jehu N.; Galvan, Michelle J.; Min, Kisuk; Agullo, Francisco J.; Wagler, Amy; Bajpeyi, Sudip (Frontiers in Endocrinology, 2023)
Background Physical inactivity increases the risk for metabolic diseases such as obesity and type 2 diabetes. Neuromuscular electrical stimulation (NMES) is an effective method to induce muscle contraction, particularly for populations with physical impairments and/or metabolic diseases. However, its effectiveness to improve glycemic control is unclear. This review aimed to determine the effectiveness of NMES on glycemic control. Methods Electronic search consisted of MEDLINE (PubMed), EMBASE, Cochrane Library, Google Scholar, and Web of Science to identify studies that investigated the effects of NMES on glycemic control for this systematic review. The meta-analysis consists of the studies designed as randomized controlled trials. Effect sizes were calculated as the standardized mean difference (SMD) and meta-analysis was conducted using a random-effects model. Results Thirty-five studies met the inclusion criteria for systematic review and of those, nine qualified for the meta-analysis. Existing evidence suggested that NMES effectively improves glycemic control predominantly in middle-aged and elderly population with type 2 diabetes, obesity, and spinal cord injury. The meta-analysis is comprised of 180 participants and reported that NMES intervention lowered fasting blood glucose (SMD: 0.48; 95% CI: 0.17 to 0.78; p=0.002; I²=0%). Additional analysis using the primary measures reported by each study to indicate glycemic control (i.e., OGTT, HOMA-IR, and fasting glucose) also confirmed a significant effect of NMES on improving glycemic control (SMD: 0.41; 95% CI, 0.09 to 0.72; p=0.01; I²=11%). NMES protocol varied across studies and requires standardization. Conclusion NMES could be considered as a therapeutic strategy to improve glycemic control in populations with physical impairments and/or metabolic disorders. Systematic review registration https://www.crd.york.ac.uk/prospero/, identifier CRD42020192491.